Adolescence - Santrock, John W. (McGraw-Hill, 1998)
When [the author] wrote the first edition of [the book], [he] wanted to construct a book that would portray the study of adolescent development in an interesting and scientific manner.... [The book] is an up-to-date presentation in the three primary domains of adolescent development: biological processes, cognitive processes, and socioemotional processes. -Pref.